Terezija Vajngerl - Tetka - Ratej, Mateja (Zgodovina za vse, 2025)
The author focuses on the life of the Maribor housewife Terezija Vajngerl (1913-1997), who was strongly marked by the Second World War, when she proved to be a bold and courageous courier of the Liberation Front for Prlekija and Slovenske gorice, and by the post-war establishment of a new social order, when in 1949 she was subjected to a Cominform (Informbiro) show trial on the charge of inter-war collaboration with the Gestapo. The accusation concerned her contact with the Gestapo interpreter Hans Gerniak, a pre-war Maribor Hitlerite, through whom, as a courier, Tetka protected herself and her relatives after being compromised by the Gestapo, while at the same time obtaining information for the resistance movement. Her case, which resulted in her acquittal after numerous favorable testimonies from former OF collaborators, was closely linked to the prosecution of the main organiser of the resistance movement in Maribor in 1943-44, Dušan Špindler, whose courier she was.
Keywords: 1941-1945; Cominform; Informbiro; Maribor; odporniško gibanje; Prlekija; resistance movement; Špindler, Dušan; Vajngerl, Terezija